GAME BASED LEARNING BERBASIS QUIZIZZ SEBAGAI INOVASI MEDIA PEMBELAJARAN DI ERA NEW NORMAL (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The COVID-19 pandemic that has hit the whole world has had various impacts, including in the field of education. All levels of education, including at the elementary school level, cannot carry out teaching and learning activities face-to-face, so a learning innovation is needed so that teaching and learning activities in schools can continue. In contrast to the current situation, several schools have implemented face-to-face learning but with strict health protocols, so that there is a transition period from online learning to offline again but in a limited way because it is still in the new normal stage. Therefore, the preparation of this research proposal was carried out with the aim of knowing learning innovations that can be applied by educational institutions at the elementary school level in the new normal era, considering that the pandemic has not ended so that learning activities are carried out in various ways according to conditions. The research method uses the 4D method (Define, Design, Develop and Disseminate) with data collection techniques in the form of interviews and observations